Efektifitas Tactikal Games Model Dalam Kurikulum Merdeka Pada Permainan Tradisional Terhadap Tingkat Kebugaran Jasmani Siswa Sekolah Menengah Pertama - Terbit Surya Surya; Ega Trisna Rahayu; Resty Gustiawati (Universitas Singaperbangsa Karawang, 2023)
The problem in this study is the saturation of the actual learning model used so that when learning takes place they are not focused and feel bored and the low level of physical fitness of students at SMP Negeri 1 Branch Bungin. The purpose of this research is to find out how effective the tactical game model is in independent learning to help junior high school students learn traditional games and improve their physical fitness. The study used a quantitative approach to the experimental method with a one group pre-test post-test design. The sample uses a saturated sample technique where if all members of the population are used as a sample, there are as many as 24 children. The results of the hypothesis test use the t-test. It is known that the value of Sig. (2-tailed) of 0.000 <0.05, it can be concluded that there is a significant difference between the results of the pre-test and post-test. In traditional sports learning on students' physical fitness is acceptable, the tactical game learning model is declared effective because the value the overall N-Gain average in the N-Gain increase test was 0.54, or the increase was in the effective category.